PENYULUHAN PENGENALAN ANTI FRAUD BAGI SISWA/I SMA DAN SMK SEBAGAI UPAYA PENCEGAHAN TINDAKAN KECURANGAN - Ilham Ramadhan Ersyafdi; Habsyah Fitri Aryani; Nurul Fauziyyah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2021)
This paper is a paper written based on the results of the implementation of Community Service for 190 students and several teachers at SMA Muhammadiyah 23 Jakarta and SMK Bina Harapan Ciseeng. The aim of this socialization is to provide an understanding of the various acts of fraud, dangers, and losses due to fraud. Moreover, students are able to instill anti-fraud character and attitude since school. In the implementation of this Community Service, there is a pre-test to find out studentsâ€™ level of knowledge about fraud and the materials were delivered by andragogy method, which is a combination of lecture, discussion, and question and answer methods. Thus, the activity ended with a documentation session and providing souvenirs for the best questioners and answerers. The results obtained are that the term â€œfraudâ€ and the level of understanding about fraud are still not familiar enough among these students so that through this activity it is hoped that they will be able to think and act ethically and help reduce, prevent, and eradicate fraud in the future.